HUBUNGANKETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 7 PADANG - Simanjuntak, Nurmina; Thahar, Harris Effendi; Afnita, Afnita (Universitas Negeri Padang, 2018)
ABSTRACT There are three objectives of this research. First, to describe the skills of reading comprehension among students of grade VII at SMPN 7 Padang. Second, to describe the skills of descriptive text writing among students of grade VII at SMPN 7 Padang. Third, to describe the relationship between the skills of reading comprehension and descriptive text writing among students of grade VII at SMPN 7 Padang. The type of this research is quantitative whereas the method applied is correlational. The population of this research is students of grade VII registered in the 2017/2018 academic year with a total amount of 249 students spread over eight classes. The number of sample of this research is 40 students (15% of total population of students in each class). The sampling technique applied in the research is the proportional-random sampling. The variable of the research is the skill in reading comprehension as independent variable and the skill of descriptive text writing as bound variable. The instrument used in the research is the objective tests comprised of reading comprehension test and working test i.e. descriptive-text writing test. The data of the research is the scores of the objective tests. The gathered data was analyzed based on the indicators to obtain students' scores and points. Data analysis requirement test is the normality and homogenity test. The following are the two results of the research. First, the skill of reading comprehension among students of grade VII at SMPN 7 Padang is at a good qualification with an average score of 83.30. Second, the skill of descriptive text writing among students of grade VII at SMPN 7 Padang is at a good qualification with a score of 81.93. The result of research indicates that the skill of reading comprehension among students of grade VII at SMPN 7 Padang has significant relations to the skill of descriptive text writing. Hence, the skill of descriptive text writing requires the skill of reading comprehension. Kata kunci: membaca pemahaman, menulis, teks deskripsi